Overexpression of arginase gene CAR1 renders yeast Saccharomyces cerevisiae acetic acid tolerance - Liang Xiong; Ya-Ting Wang; Ming-Hai Zhou; Hiroshi Takagi; Jiufu Qin; Xin-Qing Zhao (Synthetic and Systems Biotechnology)
Acetic acid is a common inhibitor present in lignocellulose hydrolysate, which inhibits the ethanol production by yeast strains. Therefore, the cellulosic ethanol industry requires yeast strains that can tolerate acetic acid stress. Here we demonstrate that overexpressing a yeast native arginase-encoding gene, CAR1, renders Saccharomyces cerevisiae acetic acid tolerance. Specifically, ethanol yield increased by 27.3% in the CAR1-overexpressing strain compared to the control strain under 5.0 g/L acetic acid stress. The global intracellular amino acid level and compositions were further analyzed, and we found that CAR1 overexpression reduced the total amino acid content in response to acetic acid stress. Moreover, the CAR1 overexpressing strain showed increased ATP level and improved cell membrane integrity. Notably, we demonstrated that the effect of CAR1 overexpression was independent of the spermidine and proline metabolism, which indicates novel mechanisms for enhancing yeast stress tolerance. Our studies also suggest that CAR1 is a novel genetic element to be used in synthetic biology of yeast for efficient production of fuel ethanol.